Enhancement of ultrasound assisted aqueous extraction of polyphenols from waste fruit peel using dimethyl sulfoxide as surfactant: Assessment of kinetic models. (January 2021) - Selvakumar, P.; Karthik, V.; Kumar, P. Senthil; Asaithambi, P.; Kavitha, S.; Sivashanmugam, P.
Abstract: Pomegranate peel, a major waste from the food processing industries containing biologically active compounds, could be converted into value-added products having medicinal properties. Present study deals with the ultrasound-assisted surfactant, namely dimethyl sulfoxide (DMSO) aided polyphenolics extraction from pomegranate peel waste using double distilled water (DDW) as a solvent. Maximum total yield of extraction and total polyphenolic content (TPC) were found respectively to be 43.58 ± 1.0 and 49.55 ± 0.8%, at optimized sonication parameters viz. temperature 50 °C, power density 1.2 W/mL and time 40 min followed by surfactant aided extraction under optimum conditions 0.6% DMSO, 50 °C and 150 rpm for 90 min. Kinetic models were developed to determine the polyphenolics concentration and validated. GC-MS analysis of the extract revealed 22 phenolic compounds. Thus, the acquired results have ensured the significance of ultrasound pre-treated surfactant aided extraction of polyphenolic compounds and this process can be developed for commercial production. Graphical abstract: Image 1 Highlights: Polyphenolic constituents are rich in pomegranate peels. Ultrasound-assisted surfactant aided extraction enhanced polyphenolics yield. Kinetic models were developed to predict polyphenolics concentration. Obtained maximum polyphenolic content in the extract was 49.55 ± 0.8%. GC-MS analysis of extract revealed 22 value-added polyphenolic compounds.